ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN KUPANG - Adechandra Lada; Rosmiati Rosmiati; Selfisina Samadara (P3M- Politeknik Negeri Kupang, 2021)
The financial performance of the Kupang Regency local government is important information in making a positive and transparent regional financial management policy for the welfare of the community. One of the tools for analyzing the financial performance of local governments in managing regional finances is by analyzing financial ratios. This study aims to analyze the financial performance of the Kupang Regency regional government in 2014-2019. This research is a quantitative descriptive study conducted at the Regional Financial and Asset Management Agency of Kupang Regency. Collecting data using interviews, documentation and literature study. The data analysis technique used is descriptive quantitative with financial ratio formulas.The results of the analysis show that the Financial Performance of the Kupang Regency Regional Government is measured by (1) the ratio of the degree of fiscal decentralization is considered very poor, (2) the ratio of the Regional Finance Ministry is considered very low, (3) Regional Dependency Ratio rated very high (4) PAD Effectiveness Ratio is considered very effective (5) PAD Efficiency Ratio considered to be efficient (6) the effectiveness ratio of local taxes is considered very effective (7) the efficiency ratio of local taxes is considered efficient, (8) BUMD's Contribution Degree Ratio is considered sufficient to contribute